Regulatory T Cells in Autoimmune and Viral Chronic Hepatitis. (28th May 2015) - Lapierre, Pascal; Lamarre, Alain
Abstract : In both autoimmune liver disease and chronic viral hepatitis, the injury results from an immune-mediated cytotoxic T cell response to liver cells. As such, it is not surprising that CD4 + regulatory T cells, a key regulatory population of T cells able to curb immune responses, could be involved in both autoimmune hepatitis and chronic viral hepatitis. The liver can induce the conversion of naïve CD4 + T cells to CD4 + regulatory T cells and induce tolerance to locally expressed antigens. This tolerance mechanism is carefully regulated in physiological conditions but any imbalance could be pathological. An overly tolerant immune response can lead to chronic infections while an overreactive and unbridled immune response can lead to autoimmune hepatitis. With the recent advent of monoclonal antibodies able to target regulatory T cells (daclizumab) and improve immune responses and several ongoing clinical trials analysing the impact of regulatory T cell infusion on autoimmune liver disease or liver transplant tolerance, modulation of immunological tolerance through CD4 + regulatory T cells could be a key element of future immunotherapies for several liver diseases allowing restoring the balance between proper immune responses and tolerance.